The presence of secondary creep in historic masonry constructions: A hidden problem. (December 2017) - Sánchez-Beitia, S.; Luengas-Carreño, D.; Crespo de Antonio, M.
Abstract: Top-ranked European research groups have been working for years on the problem of identifying the behavior of load-bearing elements due to creep in historic masonry structures. All analyses carried out were performed in unexpected structural collapses, related with earthquakes or not, in several regions all around Europe. These collapses are related with the presence of appreciable size cracks, which appear more or less vertical in towers, vaults and pillars. Although these cracks can be easy detected through mortar before the collapse, the proximity of the structure failure is not fully defined nowadays. The paper deals with the presence of another crack typology in stonework masonry blocks, which has not yet been taken into consideration. Despite they sometimes can through the blocks vertically, this second type cracks are difficult to detect owing to their reduced size and because they are under surface patina. In this sense, several real cases are presented where these cracks were found. In the laboratory work sandstone masonry blocks were subjected to a cyclic load to generate this kind of cracks, with the aim to propose a method to evaluate them in situ, before the building collapse. The proposed methodology is based on the procedures employed in the field of the quantitative metallography. Although the relation between both types of cracks is not clear, the possibility that small ones coalesce to the bigger ones is suggested. The small typology cracks appear due to long-term loads, which are associated with cyclical loads. In other words, it is a fracture caused by creep-fatigue interaction. This work aims to point out the probable existence of these cracks hidden under stonework masonry blocks surface, in a great number of historical constructions. These small size cracks would correspond to the secondary creep. When these cracks reach the edge of the blocks, bigger cracks appear in the mortar, causing the tertiary creep. Highlights: The methods of the quantitative metallography for quantify the size and number of cracks are useful in masonry. The paper deals with creep phenomenon in masonry constructions. The possibility of detecting secondary creep in historical constructions is being researched. Minor fissures have been detected and they may be the origin of bigger cracks in historical constructions. A new method is proposed in order to detect those first minor fissures in masonry.